Respuesta :

Answer:

The answer is  a= [tex]\frac{8x^2+11x+1}{2}[/tex]

Step-by-step explanation:

Combine like terms and we get,

[tex]24x^2+83x+3=6ax[/tex]

[tex]\frac{24x^2+33x+3}{6x} =a[/tex]             divide both sides of the equation by ax, and simplify further,

[tex]\frac{x(8x^2+11x+1)}{2}[/tex]                          notice that we can reduce the 24 over 6 1/2,

[tex]\frac{8x^2+11x+1}{2} =a[/tex]                 distribute and simplify further

And a=[tex]\frac{8x^2+11x+1}{2}[/tex]

ACCESS MORE